Adsorption and characterization of MCPA on DDTMA- and raw-montmorillonite: surface sites involved - Santiago, Cintia C. (2016)
The 4-chloro-2-methylphenoxy acid (MCPA) is an herbicide widely used in agriculture, which generates a great concern about contamination of surface water and serious consequences for human health and the environment. In this work, the adsorption of MCPA on an Argentine montmorillonite (MMT) and its organo-montmorillonite product (OMMT) with different dodecyl trimethyl ammonium loading was investigated. MCPA adsorption on OMMT increases at least 3 times, with respect to the amount determined for MMT. X-ray diffraction and zeta potential analyses indicated the inner (interlayer) and outer surface participate as adsorption sites. Changes in surface electric charge and also interlayer expansion suggest that dimethyl amine (MCPA counterion) was also surface-adsorbed. The larger aggregates of OMMT, without and with MCPA, obtained compared to those of MMT samples, generate an improvement in the coagulation efficiency. This property, particularly after MCPA retention, allows an easier separation of the solids from the solution and enables a simple technological process application.